Capital transfer tax - Walters, R. M. (Stockport, Eng. : Polytech, 1980)
This book has been primarily written for those who need to know the details of the Capital Transfer Tax. There are now twenty-two further questions based largely on questions set by professional bodies. This fourth edition incorporates amendments made by the Finance Act 1980 and includes a summary of the most important points at the end of each chapter.
Includes index.
ne 06/09/2019
Loans
Keywords: Inheritance and transfer tax; Gifts--Taxation.